The Annealing Kinetics of Defects in CVD Diamond Irradiated by Xe Ions - Kotomin, Eugene A.; Kuzovkov, Vladimir N.; Lushchik, Aleksandr; Popov, Anatoli I.; Shablonin, Evgeni; Scherer, Theo; Vasil’chenko, Evgeni (MDPI, 2024)
The radiation-induced optical absorption at 1.5–5.5 eV (up to the beginning of fundamental absorption) has been analyzed in CVD diamond disks exposed to 231-MeV 132Xe ions with four fluences from 1012 to 3.8 × 1013 cm−2. The 5 mm diameter samples (thickness 0.4 mm) were prepared by Diamond Materials, Freiburg (Germany); the average grain size at growth site was around 80 μm; and the range of xenon ions was R = 11.5 μm. The intensity of several bands grows with ion fluence, thus confirming the radiation-induced origin of the defects responsible for these bands. The recovery of radiation damage has been investigated via isochronal (stepwise) thermal annealing procedure up to 650 °C, while all spectra were measured at room temperature. Based on these spectra, the annealing kinetics of several defects, in particular carbon vacancies (GR1 centers with a broad band ~2 eV) and complementary C-interstitial-related defects (~4 eV), as well as impurity-related complex defects (narrow bands around 2.5 eV) have been constructed. The experimental kinetics have also been analyzed in terms of the diffusion-controlled bimolecular reactions. The migration energies of tentatively interstitial atoms (mobile components in recombination process) are obtained, and their dependence on the irradiation fluences is discussed. © 2024 by the authors. This is an open-access article Kotomin, E.A.; Kuzovkov, V.N.; Lushchik, A.; Popov, A.I.; Shablonin, E.; Scherer, T.; Vasil’chenko, E. The Annealing Kinetics of Defects in CVD Diamond Irradiated by Xe Ions. Crystals 2024, 14, 546. https://doi.org/10.3390/cryst14060546 published under the CC BY 4.0 licence.
This study was supported by EUROfusion Enabling Research Project ENR-MAT.01.UT-T001-D001 "Investigation of defects and disorder in nonirradiated and irradiated Doped Diamond and Related Materials for fusion diagnostic applications (DDRM) Theoretical and Experimental analysis." This work has been carried out within the framework of the EUROfusion Consortium, funded by the European Union via the Euratom Research and Training Programme (Grant Agreement No 101052200 EUROfusion). Views and opinions expressed are, however, those of the author(s) only and do not necessarily reflect those of the European Union or the European Commission. Neither the European Union nor the European Commission can be held responsible for them. The research was partly performed in the Center of Excellence of the Institute of Solid State Physics, University of Latvia, supported through European Union\u2019s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; CVD diamond; diffusion-controlled reactions; Frenkel defects; interstitial ions; irradiation; optical absorption; swift heavy ions; thermal annealing; Xe